A Nuclear Reactor Transient Methodology Based on Discrete Ordinates Method - Shun Zhang; Bin Zhang; Penghe Zhang; Hui Yu; Yixue Chen (Science and Technology of Nuclear Installations)
With the rapid development of nuclear power industry, simulating and analyzing the reactor transient are of great significance for the nuclear safety. The traditional diffusion theory is not suitable for small volume or strong absorption problem. In this paper, we have studied the application of discrete ordinates method in the numerical solution of space-time kinetics equation. The fully implicit time integration was applied and the precursor equations were solved by analytical method. In order to improve efficiency of the transport theory, we also adopted some advanced acceleration methods. Numerical results of the TWIGL benchmark problem presented demonstrate the accuracy and efficiency of this methodology.